Legal Reform on Rehabilitation for Drug Users as an Ultimum Remedium Effort - Jaya, Candra; Hikmah, Faidatul (JURNAL USM LAW REVIEW, 2024)
This study explores Indonesia's legal approach to narcotics rehabilitation under Law Number 35 of 2009, focusing on a shift from punitive measures to a public health framework. Article 54 mandates both medical and narcotics rehabilitation for addicts, emphasizing a commitment to breaking the cycle of dependency. Through analyzing legal provisions, Supreme Court circulars, and joint regulations, this research highlights a three-stage rehabilitation process: medical, non-medical, and aftercare phases. Emphasizing rehabilitation over punishment, insights align with the ultimum remedium principle, advocating for alternative policies. Results reveal a progressive legal landscape recognizing narcotics users as individuals in need of treatment. Supreme Court circulars and joint regulations aim to address challenges, emphasizing the importance of collaboration between legal, health, and social entities for an effective narcotics rehabilitation system in Indonesia. This legal mandate signifies a pivotal shift towards a holistic, public health-oriented response to narcotics offenses, reflecting an acknowledgment of addiction's multifaceted nature. Ongoing collaboration is crucial for successfully integrating rehabilitation into the legal framework, ensuring a compassionate and effective response to narcotics-related issues.